How Does Fearful Emotion Affect Visual Attention? - Shang, Zhe; Wang, Yingying; Bi, Taiyong (Frontiers in Psychology, 2021)
It has long been suggested that emotion, especially threatening emotion, facilitates early visual perception to promote adaptive responses to potential threats in the environment. Here, we tested whether and how fearful emotion affects the basic visual ability of visual acuity. An adapted Posner’s spatial cueing task was employed, with fearful and neutral faces as cues and a Vernier discrimination task as the probe. The time course of the emotional attention effect was examined by varying the stimulus onset asynchrony (SOA) of the cue and probe. Two independent experiments (Experiments 1 and 3) consistently demonstrated that the brief presentation of a fearful face increased visual acuity at its location. The facilitation of perceptual sensitivity was detected at an SOA around 300ms when the face cues were presented for both 250 ms (Experiments 1) and 150 ms (Experiments 3). This effect cannot be explained by physical differences between the fearful and neutral faces because no improvement was found when the faces were presented inverted (Experiment 2). In the last experiment (Experiment 4), the face cues were flashed very briefly (17 ms), and we did not find any improvement induced by the fearful face. Overall, we provide evidence that emotion interacts with attention to affect basic visual functions.